Adsorption of Mercury(II) by Beer Yeast Immobilized in Chitosan/Silicone Leg - Hai, Reti; Feng, Hong; Wang, Wenxing (Asian Journal of Chemistry, 2013)
Highly toxic Hg(II) can harm human health seriously and there are many studies on adsorbents to adsorb Hg(II) in water phase. In this test, chitosan, silica gel and beer yeast were used to prepare a new adsorbent to adsorb a small quantity of Hg(II) from water and then the effects of solution pH, contact time, adsorbent dosage and temperature on the adsorption effect of Hg(II) were analyzed. The results showed that when adsorbent dosage was 0.4 g/L, contact time was 40 min and the initial concentration of Hg(II) was 5 mg/L, the removal rate of Hg(II) reached 99.34 %. However, temperature has no obvious effects on Hg(II) adsorption.